Savage Carrot - Tomey, Ingrid (New York : Maxwell Macmillan International, 1993)
Thirteen-year-old Carrot tries to come to terms with the sudden death of her father and the family's new life on her grandmother's farm.
Booklist.
Horn Book.
School Library Journal.
5.5.
5.5
5-8
Keywords: Death -- Fiction; Family problems -- Fiction; Farm life -- Fiction; Grief -- Fiction; Death -- Fiction; Family problems -- Fiction; Farm life -- Fiction; Joy and sorrow -- Fiction